Humidity responsivity of CYTOP-XYLEX fibre Bragg grating sensors - Ioannou, Andreas; Posporis, Andreas; Kalli, Kyriacos (My University, 2023)
CYTOP-XYLEX fibre Bragg grating (FBG) sensors’ response to relative humidity (RH) changes is investigated in this work. The intensive research on CYTOP polymer optical fibre sensors relies on their lower optical attenuation compared with the standard poly(methyl) methacrylate (PMMA) based polymer optical fibre sensors. However, CYTOP is a hydrophobic polymer and cannot be used as a standalone material in humidity-sensing applications. A hydrophilic material is required to be used as fibre over-cladding for RH detection; the water swelling occurring in the over-cladding material can strain the FBG structure located in the CYTOP core. In this work, a novel CYTOP fibre with a XYLEX over-cladding material is used to investigate the humidity responsivity of FBG sensors. A femtosecond laser system and the plane-by-plane inscription method were utilised to fabricate the FBG sensors through the fibre over-cladding. The FBG sensors were placed in a climatic chamber with controlled temperature and RH, and their response to RH changes was monitored. The RH sensitivity was evaluated for different temperatures. The results show that the RH sensitivity increases with temperature, whereas the reported RH sensitivity of PMMA-based sensors decreases with temperature. We also report that by applying a pre-strain on the fibre, the RH sensitivity can be eliminated for cross-sensitivity compensation purposes.
Keywords: CYTOP; fibre Bragg grating sensors; humidity sensitivity; Polymer optical fibre; XYLEX